Reactive nitrogen in Mexico City and its relation to ozone-precursor sensitivity: results from photochemical models - S. Sillman; J. J. West (Atmospheric Chemistry and Physics, 2009)
We use results of a 3-D photochemistry/transport model for ozone formation in Mexico City during events in 1997 to investigate ambient concentrations of reactive nitrogen in relation to ozone-precursor sensitivity. Previous results from other locations suggest that ratios such as O3/NOy and H2O2/HNO3 might provide measurement-based indicators for NOx-sensitive or VOC-sensitive conditions. Mexico City presents a different environment due to its high concentrations of VOC and high level of pollutants in general. The model predicts a correlation between PAN and O3 with relatively high PAN/O3 (0.07), which is still lower than measured values. The model PAN is comparable with results from a model for Paris but much higher than were found in Nashville in both models and measurements. The difference is due in part to the lower temperature in Mexico City relative to Nashville. Model HNO3 in Mexico City is unusually low for an urban area and PAN/HNO3 is very high, probably due to the high ratio of reactivity-weighted VOC to NOx. The model predicts that VOC-sensitive chemistry in Mexico is associated with high NOx, NOy and NOx/NOy and with low O3/NOy and H2O2/HNO3, suggesting that these indicators work well for Mexico City. The relation between ozone-precursor sensitivity and either O3/NOz or O3/HNO3 is more ambiguous. VOC-sensitive conditions are associated with higher O3/HNO3 than would be found in NOx-sensitive conditions, but model O3/HNO3 associated with both NOx-sensitive and VOC-sensitive chemistry is higher in Mexico than in other cities. The model predicts a mixed pattern of ozone-precursor sensitivity in Mexico City, with VOC-sensitive conditions in the morning and NOx-sensitive in the afternoon, in contrast to results from other models for more recent events that predicted strongly VOC- sensitive conditions throughout the day. The difference in predicted ozone-precursor sensitivity is most likely due to different emission rates and to changes in emissions over time. The model with mixed sensitivity predicts much lower ambient NOx and NOx/NOy than the strongly VOC-sensitive model.